2014
DOI: 10.1177/0961203314546018
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant systemic vasculitis in systemic lupus erythematosus. Case report and review of the literature

Abstract: Vasculitis in systemic lupus erythematosus (SLE) has a broad spectrum of clinical manifestations from cutaneous to visceral involvement and its prognosis ranges from mild to life-threatening. We report the case of a previously healthy 17-year-old woman with eight months' history of arthralgias and myalgias. Subsequently, she developed facial and lower limbs edema, and hair loss. Two weeks before admission to a secondary level hospital, she developed fever up to 40°C followed by abdominal pain, rectal bleeding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Highdose glucocorticoids have been recommended as the initial treatment for Takayasu's arteritis or giant cell arteritis, which are major types of aortitis (34,35). However, fatal cases of lupus aortitis without aortic dissection or aortic aneurysm despite high-dose glucocorticoid administration have been reported (25,26). Since heterogeneous outcomes have been reported and there have been no controlled trials, the need for high-dose glucocorticoids as the initial treatment for lupus aortitis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Highdose glucocorticoids have been recommended as the initial treatment for Takayasu's arteritis or giant cell arteritis, which are major types of aortitis (34,35). However, fatal cases of lupus aortitis without aortic dissection or aortic aneurysm despite high-dose glucocorticoid administration have been reported (25,26). Since heterogeneous outcomes have been reported and there have been no controlled trials, the need for high-dose glucocorticoids as the initial treatment for lupus aortitis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the infection-associated injury could induce tissue acidosis, which is reflected in ABI as base excess or base deficit [36]. Other studies have reported scrub typhus-induced vasculitis to be related to ABI [37,38,39,40,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous vasculitis often responds to antimalarials (hydroxychloroquine), dapsone or thalidomide. Short courses of corticosteroids may be used if a rapid response is desired [45]. For visceral involvement, intravenous methylprednisolone pulse therapy or high-dose prednisone have been reported to be useful [46], and has been administered along with other immunosuppressants, mainly cyclophosphamide or rituximab as induction therapy, and varying regimens of azathioprine, mycophenolate mofetil, and hydroxychloroquine used for maintenance [47][48][49].…”
Section: Lupusmentioning
confidence: 99%